2011
DOI: 10.1080/17461391.2011.635811
|View full text |Cite
|
Sign up to set email alerts
|

Acute caffeine ingestion enhances strength performance and reduces perceived exertion and muscle pain perception during resistance exercise

Abstract: The efficacy of caffeine ingestion in enhancing aerobic performance is well established. However, despite suggestions that caffeine may enhance resistance exercise performance, research is equivocal on the effect of acute caffeine ingestion on resistance exercise performance. It has also been suggested that dampened perception of perceived exertion and pain perception might be an explanation for any possible enhancement of resistance exercise performance due to caffeine ingestion. Therefore, the aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
104
6
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(124 citation statements)
references
References 34 publications
10
104
6
4
Order By: Relevance
“…The results showed that consumption of 5 mg/kg caffeine compared with placebo reduced RPE and perceptions of pain after muscular endurance test, which is in agreement with a range of preceding studies (Backhouse et al, 2011;Doherty, Smith, 2005;Duncan et al, 2013) and is contrast to studies reporting no significant reductions of RPE and perceptions of pain after tests following acute caffeine ingestion (Astorino et al, 2011b;Astorino, Roupoli, Valdivieso, 2012).…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…The results showed that consumption of 5 mg/kg caffeine compared with placebo reduced RPE and perceptions of pain after muscular endurance test, which is in agreement with a range of preceding studies (Backhouse et al, 2011;Doherty, Smith, 2005;Duncan et al, 2013) and is contrast to studies reporting no significant reductions of RPE and perceptions of pain after tests following acute caffeine ingestion (Astorino et al, 2011b;Astorino, Roupoli, Valdivieso, 2012).…”
Section: Discussioncontrasting
confidence: 43%
“…Also, Duncan et al (2013) and Backhouse et al (2011) demonstrated that moderate dose (6 mg/kg) of caffeine ingested 1 h prior to exercise was associated with a maintenance effect in relation to feelings of pleasure and lowered perceptions of effort and RPE reduction. The study of Duncan et al (2013) showed that RPE was significantly lower during upper body exercises compared to lower body exercises. Also, muscle pain perception was lower in the caffeine condition, irrespective of exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the impact of caffeine upon short duration high intensity activity remains unclear; with some studies showing no effect or even a performance decrement with caffeine supplementation [61][62][63]. Duncan et al however, reported that number of repetitions completed was higher when caffeine was ingested 60 min pre-RE [64]. This suggests that total work was higher in the caffeine condition.…”
Section: Caffeinementioning
confidence: 88%
“…On the other hand, both supporting [12][13][14][15][16][17][18] and contradicting [19][20][21][22][23] research has been published in terms of muscular endurance. Furthermore, the evidence of caffeine improving muscular strength is a concept that produces additional equivocal conclusions.…”
mentioning
confidence: 98%